EFEKTIVITAS KEWENANGAN BAWASLU DALAM PENEGAKAN HUKUM PEMILU: STUDI EMPIRIS PEMILU 2024 DI KABUPATEN KARAWANG - Rizal Fuad Muttaqin; Urip Giyono (CV. Barokah Publsiher, 2026)
General elections constitute the primary instrument for realizing constitutional democracy and popular sovereignty in Indonesia. In their implementation, the effectiveness of election law enforcement is a crucial factor in ensuring the conduct of free and fair elections. The General Election Supervisory Agency (Bawaslu) holds strategic authority in supervising, preventing, and taking action against electoral violations. However, in practice, the 2024 General Election still witnessed various violations, indicating that the effectiveness of election law enforcement has not yet been fully optimized. This study aims to analyze the effectiveness of Bawaslu’s authority in enforcing election law during the 2024 General Election in Karawang Regency and to identify the factors influencing such effectiveness. The research employs an empirical legal research method with a qualitative approach. Data were collected through interviews, observations, and documentation studies related to the implementation of Bawaslu’s authority in election law enforcement. The collected data were analyzed descriptively and analytically to understand how Bawaslu’s authority was exercised in the practice of election administration. The findings indicate that Bawaslu’s authority in election law enforcement falls within the category of being moderately effective. This effectiveness is influenced by several factors, including regulatory frameworks, the quality of human resources, coordination among election law enforcement institutions, the availability of facilities and infrastructure, as well as the level of public participation and legal awareness. The study emphasizes that institutional strengthening, capacity building of human resources, and the optimization of inter-agency coordination are strategic measures for enhancing the effectiveness of election law enforcement in a manner that upholds integrity and democratic principles.